State-Of-Research on Performance Indicators for Bridge Quality Control and Management - Zanini, Mariano Angelo; Faleschini, Flora; Casas, Joan Ramon (Frontiers in Built Environment, 2019)
The present study provides a review of the most diffused technical and non-technical performance indicators adopted worldwide by infrastructure owners. This work, developed within the European COST Action TU 1406 – “Quality specifications for roadway bridges, standardization at a European level”, aims to summarize the state-of-art maintenance scheduling practices adopted by bridge owners, mainly focusing on the identification and classification of the most diffused performance indicators (PIs). PIs are subdivided in technical and non-technical ones: for this latter subclass, PIs are classified in environmental, social and economic-targeted. The study aims to be a reference for researchers dealing with performance-based assessments and bridge maintenance and management practices.